2017
DOI: 10.1055/s-0037-1603498
|View full text |Cite
|
Sign up to set email alerts
|

Skin Color and Maternal Near Miss: Exploring a Demographic and Health Survey in Brazil

Abstract: Keywords► severe maternal morbidity ► maternal near miss ► pregnancy complications ► ethnicity ► maternal and child health AbstractPurpose In 2013, it was estimated that 289,000 maternal deaths occurred worldwide. The maternal mortality ratio has decreased in many countries in the past decades, due to early identification and treatment of obstetric complications, despite the dissimilarities observed in diverse locations and populations. Black women, for instance, have always been more susceptible to the occurr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 18 publications
0
2
0
1
Order By: Relevance
“…Ethnic disparities in birth outcomes have modestly been studied compared to other social determinants of health, such as wealth, education, age and place of residence. Several studies in high-income countries have shown that women of African descent experience a two to six times higher risk for severe maternal outcomes compared to Caucasian women (often linked to socio-economic factors) [12][13][14][15][16]. Suriname is particularly of interest as it has multiple ethnic groups without one great majority [17].…”
Section: Introductionmentioning
confidence: 99%
“…Ethnic disparities in birth outcomes have modestly been studied compared to other social determinants of health, such as wealth, education, age and place of residence. Several studies in high-income countries have shown that women of African descent experience a two to six times higher risk for severe maternal outcomes compared to Caucasian women (often linked to socio-economic factors) [12][13][14][15][16]. Suriname is particularly of interest as it has multiple ethnic groups without one great majority [17].…”
Section: Introductionmentioning
confidence: 99%
“… 12 In Brazil, the DHS goes by the name of the National Demographic and Health Survey ( Pesquisa Nacional de Demografia e Saúde - PNDS). Conducted in 1986, 1996 and 2006, the PNDS enabled assessment of changes in women’s and children’s health, 13 as well as enabling international comparisons. 14 Still with regard to ​​maternal and child health, the Being Born in Brazil - National Survey on Child Delivery and Birth ( Nascer no Brasil - Inquérito Nacional sobre Parto e Nascimento ) was conducted in 2011-2012 with the aim of investigating antenatal care, child delivery, birth and the postpartum period.…”
Section: National Health Surveysmentioning
confidence: 99%
“…12 No Brasil, o DHS é denominado de Pesquisa Nacional de Demografia e Saúde (PNDS). Realizada em 1986, 1996 e 2006, a PNDS possibilitou a avaliação das mudanças ocorridas na saúde da mulher e da criança 13 e permitiu comparações internacionais. 14 Ainda na área de saúde materno-infantil, o Nascer no Brasil -Inquérito Nacional sobre Parto e Nascimento -foi realizado em 2011-2012 com o objetivo de investigar o atendimento pré-natal, parto, nascimento e puerpério.…”
Section: Inquéritos Nacionais De Saúdeunclassified